The temptation of Realpolitik and vox populi in the ecclesiology of the Emerging Apostolic Churches with special reference to the fivefold ministry - Resane, K. Thomas (HTS teologiese studies, 2008)
The Emerging Apostolic Churches do not have a uniform church polity since the power of governance is claimed to be with the fivefold ministers, while at the same time embracing either the Episcopal, Presbyterial, or Congregational church governments. The fivefold ministry is a generally accepted term that refers to the five ministries given by Christ to the Church to stand in unique spiritual offices, as found in Ephesians 4:11. This article tries to answer the question: “Are the Emerging Apostolic Churches ecclesiologically correct by centring the authority of governance in the fivefold ministers and the popular voices of the followers?” At the same time it is endeavored to argue that due to Biblical and theological grounds the fivefold ministry is untenable to church polity hence Realpolitik and vox populi dominating the ecclesiastical life and polity of the Emerging Apostolic Churches. The aim is to demonstrate that these two concepts (Realpolitik and vox populi) play a significant part in shaping the church polity and structures of this ecclesiastical phenomenon.